2012
DOI: 10.3390/ijms131115054
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Molecular Mechanisms of the Anti-Leukemic Effects of Phenolic Compounds in Honey

Abstract: Hematologic malignancies constitute about 9% of all new cases of cancers as reported via the GLOBOCAN series by International Agency for Research on Cancer (IARC) in 2008. So far, the conventional therapeutic and surgical approaches to cancer therapy have not been able to curtail the rising incidence of cancers, including hematological malignancies, worldwide. The last decade has witnessed great research interest in biological activities of phenolic compounds that include anticancer, anti-oxidation and anti-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 82 publications
1
48
0
1
Order By: Relevance
“…The disruption of the normal cell cycle plays a vital role in the development of cancer. A large number of anticancer natural compounds have been shown to induce cell death and apoptosis in close association with cell cycle arrest at the G1 phase 9 (24)(25)(26). In this study, Jurkat and CEM-CM3 cells treated with CGE showed a significant accumulation of cells in the G1 phase; there was a concurrent reduction of the cell population in S and G2/M phase in a dose-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…The disruption of the normal cell cycle plays a vital role in the development of cancer. A large number of anticancer natural compounds have been shown to induce cell death and apoptosis in close association with cell cycle arrest at the G1 phase 9 (24)(25)(26). In this study, Jurkat and CEM-CM3 cells treated with CGE showed a significant accumulation of cells in the G1 phase; there was a concurrent reduction of the cell population in S and G2/M phase in a dose-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…We have recently reviewed the origin and characteristics of HL-60, U937, MOLT-4, NALM-6, and K562 cell lines [75]. HL-205 cells are clones of cells isolated from HL-60 cells [94].…”
Section: Introductionmentioning
confidence: 99%
“…Inspite of their significant difference in their phenolic content, % T/C values show barely discernible difference between the two honey samples. Researchers had identified some phenolic components of honey that have been attributed to the antileukemic activity [ 11 ]. Hence, we assume that qualitative nature of phenolic constituents present in the honey may play a vital role against the leukemia but not the total phenolic content of honey.…”
Section: Discussionmentioning
confidence: 99%